Preparation method of ether-ester co-soluble lithium metal battery low-temperature electrolyte and soft package battery
By using low-temperature electrolyte co-soluble ether ester in lithium metal batteries and introducing ester solvents to adjust the solvated structure of lithium ions, the problem of poor electrochemical performance of lithium metal batteries under extreme low temperature conditions is solved, and the discharge capacity and cycle stability are significantly improved.
Patent Information
- Application Number
- CN202411892123.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium metal batteries have poor electrochemical performance under extremely low temperature conditions, resulting in low discharge capacity and poor circulation performance, limiting their application in extremely low temperature environments.
The low-temperature electrolyte of lithium metal battery co-soluble is adopted. By introducing ester solvents, the solvation structure of lithium ions is adjusted, the desolvation energy of lithium ions is reduced, the transmission capacity of lithium ions is improved, and the discharge capacity and cycle stability of the battery under low temperature conditions are improved.
The discharge capacity and cycle stability of lithium metal batteries under extremely low temperature conditions have been significantly improved, and a long cycle at -40℃ has been achieved. The initial discharge capacity can reach 157.48 mAh/g. The discharge capacity of lithium metal soft-pack batteries matching the electrolyte reaches 75% of the room temperature capacity at -40℃.
Smart Images

Figure CN119833748A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to the preparation of a low-temperature electrolyte for lithium metal batteries containing ether and ester co-solvents, and a soft-pack battery. Background Art
[0002] More and more countries are taking carbon neutrality as a national strategy to alleviate the increasingly serious problems of global warming and climate change. The development of advanced energy storage technology plays an important role in accelerating the process of carbon neutrality. Among them, lithium batteries are widely used in portable electronic products, electric vehicles and other fields due to their high energy density, high efficiency and long life. But for batteries, in addition to traditional standards such as energy density, power density, fast charging capability, life, and safety, there is an urgent need to expand the operating temperature of rechargeable batteries. When the operating temperature is below -30℃, commercial lithium-ion batteries using graphite anodes suffer serious energy and power density losses due to slow reaction kinetics. Lithium metal anodes have the advantage of "ultra-high mass-energy" and their theoretical specific capacity is 3860 mAh / g. They are called the "holy grail" in the field of batteries. There is great hope for promoting battery-level energy density at sub-zero temperatures, and they have broad application space in deep sea, outer space and other fields.
[0003] However, the electrochemical performance of lithium metal batteries when working at extreme temperatures is unsatisfactory and difficult to meet the needs of practical application. This greatly limits its application in extreme low temperature environments such as high latitudes or high altitudes and in the deep sea, national defense, and outer space. Therefore, it is crucial to develop electrolytes that can be used under extreme temperature conditions.
[0004] At extreme temperatures (such as -40°C), lithium metal anodes are still limited by slow lithium ion interface kinetics and lithium dendrite growth. The impedance of lithium ion transmission in the battery mainly comes from ohmic resistance, interface resistance and charge transfer resistance. Among them, charge transfer resistance is the main impedance source of the battery under low temperature conditions and is closely related to the desolvation process of lithium ions. Electrolyte engineering is one of the most direct means to solve this problem. It has good operability and has received widespread attention from researchers. By adjusting the solvation structure of the electrolyte, adjusting the interaction between lithium ions and the solvent and the electrode / electrolyte interface properties, the discharge capacity and cycle stability of the battery under low temperature conditions are enhanced. However, the existing electrolytes still cannot meet the requirements of battery cycle performance and high discharge capacity at extreme temperatures. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention provides a low-temperature electrolyte for lithium metal batteries in which ether-ester co-solvent is used. By introducing an ester solvent to participate in the solvation structure of lithium ions, the freezing point and viscosity of the electrolyte are reduced, and a solvation structure mainly composed of contact ion pairs / aggregated ion pairs is formed, thereby reducing the desolvation energy of lithium ions under low temperature conditions, reducing the charge transfer resistance, and improving the transport capacity of lithium ions under low temperature conditions, so as to enhance the discharge capacity of the battery under low temperature conditions. In addition, the introduction of the ester solvent helps to promote the uniform deposition of lithium metal, protect the structure of the positive electrode material from being destroyed, and enhance the cycle stability of the battery under low temperature conditions. It aims to solve the problems of low discharge capacity and poor cycle performance of batteries under extreme temperature conditions.
[0006] To achieve the above object, the present invention proposes the following technical solutions: A low-temperature electrolyte for lithium metal batteries in which ether and ester are co-dissolved. The electrolyte for lithium metal batteries is composed of a lithium salt, a diluent, an ether solvent and an ester solvent. The molar concentration of the lithium salt is 1.28-1.6 mol / L. The molar ratio of the lithium salt to the ether solvent and the diluent is 1:1.2:3, and the molar ratio of the ether solvent to the ester solvent is 1:0.5-2.
[0007] The lithium salt is one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
[0008] The ether solvent used is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0009] The ester solvent is one of ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0010] The diluent is one of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, bis(2,2,2-trifluoroethyl) ether and 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether.
[0011] The molar concentration of the lithium salt is preferably 1.37-1.47 mol / L.
[0012] The molar ratio of the ether solvent to the ester solvent is 1:1-1.5.
[0013] A method for preparing an ether-ester co-solvent lithium metal battery low-temperature electrolyte comprises the following steps: in a glove box filled with a protective atmosphere, dissolving a lithium salt in an ether solvent, adding a diluent, stirring magnetically until the mixture is uniformly mixed, then adding an ester solvent, continuing magnetic stirring for 2-4 h, and mixing uniformly to obtain an ether-ester co-solvent lithium metal battery low-temperature electrolyte.
[0014] The protective atmosphere is argon or nitrogen, with an oxygen content of <0.1ppm and a water content of <0.1ppm.
[0015] A lithium metal soft-pack battery comprises a positive electrode, a negative electrode and a low-temperature electrolyte co-dissolved in ether ester, wherein the positive electrode is a nickel-cobalt-manganese layered oxide, the negative electrode is lithium metal, and the separator is a 20μm thick PP / PE / PP material separator.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The introduction of ester solvents into ether electrolytes forms locally high-concentration electrolytes, which broadens the operating voltage range of the electrolyte, improves the wettability problem of locally high-concentration electrolytes under low temperature conditions, and is conducive to the full infiltration of the electrolyte; after the introduction of ester solvents, more anions coordinate with lithium ions, and the ester solvents enter the first solvation sheath of lithium ions to form a solvation structure dominated by contact ion pairs and aggregated ion pairs, which helps the rapid desolvation of lithium ions at low temperatures and accelerates the transmission of lithium ions at low temperatures.
[0017] (2) The ether-ester co-solvent lithium metal battery low-temperature electrolyte has better compatibility with the lithium metal negative electrode, which is conducive to the uniform deposition of lithium metal, avoiding the lithium metal deposition problem caused by the high overpotential faced by the graphite negative electrode of conventional lithium-ion batteries. A protective SEI / CEI mainly composed of inorganic substances is formed on the surface of the positive and negative electrodes, which inhibits the growth of lithium dendrites and reduces the generation of positive electrode cracks. In addition, the electrolyte can achieve long-term cycling of lithium metal batteries at -40°C, and the initial discharge capacity can be as high as 157.48 mAh / g; the lithium metal soft-pack battery matching this electrolyte has a discharge capacity of 75% of the room temperature capacity at -40°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 The cycle performance of the Li / Li symmetric battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 1 and the comparative example; Figure 2 The cycle performance of the Li / NMC811 battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 1 and the comparative example; Figure 3 The cycle performance of the Li / NMC811 battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 2 and the comparative example; Figure 4 The cycle performance of the Li / NMC811 battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 3 and the comparative example; Figure 5 The cycle performance of the Li / NMC811 battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 4 and the comparative example; Figure 6 The cycle performance of the Li / NMC811 soft pack battery at -40°C of the lithium metal battery low-temperature electrolyte prepared in Example 1; Figure 7 (a) and (b) are SEM images of the low-temperature electrolyte for lithium metal batteries prepared in Example 1 and Comparative Example after 100 cycles of NMC811 at -40°C; Figure 8 (a) and (b) are SEM images of the lithium metal battery low-temperature electrolyte prepared in Example 1 and the comparative example after 100 cycles of lithium metal at -40°C. DETAILED DESCRIPTION
[0020] The raw materials used in the present invention were purchased from Suzhou Duoduo Chemical Technology Co., Ltd., Hubei Rongbai Lithium Battery Materials Co., Ltd. and Dongguan Kelude Experimental Equipment Technology Co., Ltd.
[0021] In the following embodiments, 2016 type button cells are used to assemble button cells. (1) In the lithium metal symmetric battery, the positive and negative electrodes are made of lithium sheets with a thickness of 50 μm and a diameter of 16 mm, and the separator is a 20 μm thick PP / PE / PP separator. The amount of electrolyte used in each battery is 100 μL; (2) In lithium metal batteries, a lithium sheet with a thickness of 50 μm is used as the negative electrode, with a loading of 4 mg / cm 2 LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is the positive electrode, the diaphragm is a 20μm thick PP / PE / PP diaphragm, and the electrolyte consumption for each battery is 100μL.
[0022] Li / NMC811 lithium metal soft pack battery uses 50 μm thick lithium strip as negative electrode and 10 mg / cm loading 2 LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is the positive electrode.
[0023] The only difference between each group of examples and comparative examples is that the examples contain dimethyl carbonate while the comparative examples do not contain the solvent; the difference between the examples is that the amount of dimethyl carbonate introduced is different.
[0024] Comparative Example The molar ratio of lithium bis(fluorosulfonyl)imide, ethylene glycol dimethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 1:1.2:3. The concentration of lithium salt is 1.73 mol / L. Weigh 0.46768g of lithium bis(fluorosulfonyl)imide, and according to the ratio of the three mentioned above, weigh 0.27036g of ethylene glycol dimethyl ether and 1.740525g of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The lithium metal battery electrolyte is prepared using this formula, and the steps are as follows: in a glove box filled with a protective atmosphere, dissolve the lithium salt in an ether solvent, add a diluent, and stir magnetically until the mixture is uniform to obtain a lithium metal battery electrolyte.
[0025] Example 1 A low-temperature electrolyte for lithium metal batteries in an ether-ester co-solvent, the raw materials of which are lithium salt, solvent and diluent; wherein: the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI) with a molar concentration of 1.37 mol / L. The solvent is ethylene glycol dimethyl ether (DME) and dimethyl carbonate (DMC), and the molar ratio of the two is 1:1.5. The diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE). Based on the lithium salt molar concentration of 1.37 mol / L, 0.46768 g of lithium bis(fluorosulfonyl)imide and 0.27036 g of ethylene glycol dimethyl ether were weighed; based on the molar ratio of ethylene glycol dimethyl ether to dimethyl carbonate of 1:1.5, 0.40536 g of dimethyl carbonate was weighed; based on the molar ratio of lithium salt to diluent of 1:3, 1.740525 g of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether was weighed.
[0026] The preparation method is as follows: in a glove box filled with argon atmosphere, a certain amount of lithium salt is first dissolved in DME, and then the diluent TTE is added. After being evenly mixed by magnetic stirring, DMC is added according to the molar ratio, and the magnetic stirring is continued to obtain an ether-ester co-dissolved lithium metal battery low-temperature electrolyte.
[0027] (1) The electrolyte was used in Li / Li symmetrical battery cycle performance test, the test conditions were: at -40 ° C, 0.05 mA / cm 2 The current density is 0.05 mAh / cm 2 The surface capacity is charged and discharged at constant current. The test results are as follows Figure 1 As shown, the overpotential of the symmetrical battery in Example 1 is lower than that in the comparative example, and Example 1 has higher charge conduction capability and better cycle stability; (2) The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were as follows: at 25°C, the battery was charged at a constant current rate of 0.1C (1C = 200 mA / g) to 4.35 V, then discharged at a constant current rate of 0.1C to 2.7 V. After 4 cycles, the battery was charged at a constant current rate of 0.1C to 4.35 V again. In the fully charged state, the battery was discharged at -40°C at a constant current rate of 0.1C to 2.7 V, then charged at a constant current rate of 0.1C to 4.35 V again. After constant voltage charging at 4.35 V until the current was less than 0.05C, the battery was discharged at a constant current rate of 0.1C to 2.7 V. The test results are as follows: Figure 2 As shown in FIG. 1 , at -40°C, the initial discharge capacity is 157.48 mAh / g, and after 100 cycles, the discharge capacity is 124 mAh / g, with a cycle retention rate of 76%. The positive electrode sheet and lithium metal after 100 cycles in Example 1 and the comparative example were characterized by SEM, and the results are as follows: Figure 7 and 8 As shown in FIG. 1 , it was found that cracks were generated on the surface of NMC811 after cycling in the comparative example, while almost no cracks were generated in Example 1, and the lithium metal deposition after cycling was more uniform than that in the comparative example; the test results of the assembled 2.6Ah lithium metal soft pack battery are shown in FIG. Figure 6 As shown, the initial discharge capacity at -40°C is 1.95 Ah, and the retention rate relative to room temperature is 75%.
[0028] Example 2 Same as Example 1, except that the concentration of lithium salt is 1.6 mol / L, and the molar ratio of the two is 1:0.5.
[0029] According to the molar concentration of lithium salt of 1.6 mol / L, 0.46768 g of lithium bis(fluorosulfonyl)imide was weighed, according to the molar ratio of ethylene glycol dimethyl ether to dimethyl carbonate of 1:0.5, 0.27036 g of ethylene glycol dimethyl ether and 0.13512 g of dimethyl carbonate were weighed, according to the molar ratio of lithium salt to diluent of 1:3, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether was weighed 1.740525 g. The preparation method is the same as that in Example 1.
[0030] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C, and discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, and then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7V at 0.1C. The test results are as follows: Figure 3As shown, at -40°C, the initial discharge capacity is 146.6 mAh / g, and after 100 cycles, the discharge capacity is 121.9 mAh / g.
[0031] Example 3 Same as Example 1, except that the lithium salt concentration is 1.47 mol / L, and the molar ratio of the two is 1:1. According to the lithium salt molar concentration of 1.47 mol / L, 0.46768 g of lithium bis(fluorosulfonyl)imide and 0.27036 g of ethylene glycol dimethyl ether are weighed, according to the molar ratio of ethylene glycol dimethyl ether to dimethyl carbonate being 1:1, 0.27024 g of dimethyl carbonate is weighed, and according to the molar ratio of lithium salt to diluent being 1:3, 1.740525 g of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is weighed. The preparation method is the same as Example 1.
[0032] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C, and discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, and then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7V at 0.1C. The test results are as follows: Figure 4 As shown, at -40°C, the initial discharge capacity is 146.2 mAh / g, and after 100 cycles, the discharge capacity is 115.5 mAh / g.
[0033] Example 4 Same as Example 1, except that the concentration of lithium salt is 1.28 mol / L, and the molar ratio of the two is 1:2.
[0034] According to the molar concentration of lithium salt of 1.28 mol / L, 0.46768 g of lithium bis(fluorosulfonyl)imide and 0.27036 g of ethylene glycol dimethyl ether were weighed, according to the molar ratio of ethylene glycol dimethyl ether to dimethyl carbonate of 1:2, 0.54048 g of dimethyl carbonate were weighed, according to the molar ratio of lithium salt to diluent of 1:3, 1.740525 g of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether were weighed. The preparation method is the same as that in Example 1.
[0035] The electrolyte was used for the Li / NMC811 battery cycle performance test. The test conditions were: at 25°C, the battery was charged to 4.35 V at a constant current rate of 0.1C, and discharged to 2.7 V at a constant current rate of 0.1C. After 4 cycles, the battery was charged to 4.35 V at a constant current rate of 0.1C again. In the fully charged state, the battery was discharged to 2.7 V at 0.1C at -40°C, and then charged to 4.35 V at 0.1C again. After charging at 4.35 V at a constant voltage until the current was less than 0.05C, the battery was discharged to 2.7V at 0.1C. The test results are as follows: Figure 5 As shown, at -40°C, the initial discharge capacity is 151.2 mAh / g, and after 100 cycles, the discharge capacity is 112.6 mAh / g.
[0036] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An ether-ester co-dissolved lithium metal battery low-temperature electrolyte, characterized in that: The lithium metal battery electrolyte consists of a lithium salt, a diluent, an ether solvent and an ester solvent. The molar concentration of the lithium salt is 1.28-1.6 mol / L. The molar ratio of the lithium salt to the ether solvent and the diluent is 1:1.2:3, and the molar ratio of the ether solvent to the ester solvent is 1:0.5-2.
2. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The lithium salt is one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
3. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The ether solvent used is one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
4. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The ester solvent is one of ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
5. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The diluent is one of 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl methyl ether, bis(2,2,2-trifluoroethyl) ether and 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether.
6. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The molar concentration of the lithium salt is 1.37-1.47 mol / L.
7. The ether-ester co-solvent lithium metal battery low-temperature electrolyte according to claim 1, characterized in that: The molar ratio of the ether solvent to the ester solvent is 1:1-1.
5.
8. A method for preparing an ether-ester co-solvent lithium metal battery low-temperature electrolyte as claimed in any one of claims 1 to 7, characterized in that: The steps are as follows: in a glove box filled with a protective atmosphere, dissolve the lithium salt in an ether solvent, add a diluent, stir magnetically until the mixture is evenly mixed, then add an ester solvent, continue stirring magnetically, and after mixing evenly, obtain an ether-ester co-dissolved lithium metal battery low-temperature electrolyte.
9. The method for preparing a low-temperature electrolyte for lithium metal batteries containing ether and ester according to claim 8, characterized in that: The protective atmosphere is argon or nitrogen.
10. A lithium metal soft pack battery, characterized in that: It comprises a positive electrode, a negative electrode and a low-temperature electrolyte of ether-ester co-solvent as described in any one of claims 1 to 7, wherein the positive electrode is a nickel-cobalt-manganese layered oxide, the negative electrode is lithium metal, and the separator is a 20 μm thick PP / PE / PP material separator.
Citation Information
Patent Citations
Ether ester mixed electrolyte for high-voltage lithium metal battery and application of ether ester mixed electrolyte
CN114024022A
Local high-concentration electrolyte, preparation method and application of local high-concentration electrolyte in lithium metal battery
CN114843603A
Solid polymer electrolyte with local high-concentration structure, lithium battery and method
CN117423898A
Battery electrolyte and preparation method thereof
CN117996181A
Localized high salt concentration electrolyte
WO2024145182A2